DAYA DUKUNG LIMBAH PERTANIAN TERHADAP KETERSEDIAAN PAKAN TERNAK DALAM PENERAPAN SISTEM PERTANIAN TERPADU BERBASIS TANAMAN DAN TERNAK SAPI DI DESA FATUKNUTU KECAMATAN AMABI OEFETO KABUPATEN KUPANG - Antonius Jehemat; Donatus Kantur; Fabianus Ranta (Partner, 2018)
The latest application of integrated farming system, directed to the special specification, such as technically and product specification within increase the production efficiency oriented. For this purpose, a research was conducted in Fatukanutu, Sub-distric Amabi Oefeto, Kupang regency, aboutapplication of integrated farming system model (IFS) with banana and calf based. One of the goals is to know the carrying capacity of agriculture commodity waste that cultivated on model application that potential for feed supply, they were maize waste, cabbage, white mustard and banana’s stem. For that, estimation of total available fresh waste and total dry matter and nutrition value to determine amount of calf on animal unit per year that potential to cultivate on IFS model. The result show that total fresh waste from above plant about 6,231.09 kg per year. The next, total of dry matter about 614,2 kg. This waste can use to support calf feed supply for 97 day or worth to 0.27 animal unit per year. Nevertheless, the totally carrying capacity value of the application model more high certainty, because it is not included with the other sources of roughage that’s mean Penisetum purpurephoides and Leucaena leucocephala.